If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 90 = 4x + -15 Reorder the terms: 90 + X = 4x + -15 Reorder the terms: 90 + X = -15 + 4x Solving 90 + X = -15 + 4x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + X = -15 + -90 + 4x Combine like terms: 90 + -90 = 0 0 + X = -15 + -90 + 4x X = -15 + -90 + 4x Combine like terms: -15 + -90 = -105 X = -105 + 4x Simplifying X = -105 + 4x
| 6(x+7)=20 | | R=34x-(4x+180) | | Y=x+90+4x-15 | | .1x=12.5 | | 2w=1.44 | | 12/5n=2 | | 11(x+9)=14 | | 3-3.3= | | 2a^2-4a+1=0 | | A(2)+-3=5 | | x/y=3p/2t | | 8(x+9)=14 | | x^2+95x-3000=0 | | x^3-7x^2+14x-18=0 | | 3x+4-2x=36 | | 7x-15=10x+7 | | 24=5x+10-7x | | Fx=6/2x-3 | | 8x-23=3x-3 | | 4w+3=20-1w | | 16tgx=15cosx | | 5t^2+3=9t | | 1.3=m/4.3 | | y+9=-6 | | u-4.8=7.6 | | h(-4)=3x^2-4x+4 | | 7(x+5)=15 | | (4y^7/x^3)^-2 | | X=x+58 | | p=26+n | | 6/5x7/9 | | 22.85=3x+b |